Permintaan Maaf dalam Penolakan Bahasa Indonesia yang Direalisasikan oleh Pembelajar Bahasa Inggris sebagai Bahasa Asing (EFL) yang Mahir - Eviliana, Eviliana (Kementerian Sekretariat Negara Republik Indonesia, 2014)
This article is aimed at elaborating a mostly used strategy-regret/ apology in Indonesian refusals realized by proficient English as a Foreign Language (EFL) learners. Data were taken from writer's qualitative research data in 2010 on 18 EFL learners whose TOEFL score was 450 above using Discourse Completion Test (DCT) and were analyzed by using combined refusal classification by Wannaruk (2005) and Campillo (2009) by two raters. Proficient EFL learners used regret/ apology in the initial or final position in their refusals to mitigate, to provide support for the interlocutor who was actually or potentially malaffected by a violation, and to humiliate himself or herself to some extent and to admit to fault and responsibility for a violation. This is truly culture specific and partially support Syahri's statement (2007) that Indonesian native speakers get accostumed to using 'sorry' in opening their conversations.